SIKAP PEMILIK LAHAN TERHADAP ALIH FUNGSI LAHAN PERTANIAN DI KELURAHAN WOLOAN KECAMATAN TOMOHON BARAT KOTA TOMOHON (Attitudes Of Land Owners To Agricultural Land Conversion In Woloan Village, West Tomohon Sub-District, Tomohon City) - Ezra Christabel Wynne Turambi; Rine Kaunang; Jenny Baroleh (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
The objective of this research is to determine and examine the attitudes of land owners towards the agricultural land conversion in Woloan Village, West Tomohon Subdistrict, Tomohon City. The study was conducted from September 2020 to November 2020. The data used in this study are primary and secondary. Primary data were obtained from respondents who owned land that had converted the land, while secondary data were obtained from the Central Statistics Agency, the government of Woloan Satu Village, Woloan Dua Village and related agencies. The data analysis used is descriptive analysis. The research results of this study showed that the land owner agrees to theÂ agricultural land conversion based on 3 aspects, the first is cognitive aspects, affective aspects and conative aspects. The attitude of land owners towards the conversion of agricultural land is at the index point of 67.55% and is in the good category.